Diet composition of abundant fish species in the shallow waters of the Todos os Santos Bay, Bahia, Brazil (Acta Scientiarum. Biological Sciences, 2021)
Coastal habitats have great ecological importance with estuarine environments providing feeding sites for many fish species, especially during juvenile life stages. This study investigates the diet composition and trophic guild organization of the common and abundant ichthyofauna in shallow areas of the Todos os Santos Bay (TSB), Bahia, Brazil, and their relationships with environmental parameters. Six fish sampling campaigns were carried out in the shallow zones (infralittoral) of the Paraguaçu River estuary which encompasses the inner and outer (marine exposure) reaches of the TSB. The stomach contents of 1231 individuals belonging to common and abundant species were examined. A total of 32 food items were identified and fish were into four trophic guilds: detritivores, zoobenthivores I, zoobenthivores II, and zooplanktivores. The relationship between the guilds and environmental parameters showed that zoobenthivores II and zooplanktivores guilds had a positive relationship with salinity and pH, explaining 86% of data variability, though only the salinity variable was significant. This study provides basic information about the diet composition of common and abundant species in the TSB and their organization into trophic guilds. In addition, demonstrates that shallow waters fish across all guilds have broadly similar diets, comprising food items that are usually associated with bottom waters.